2015
DOI: 10.1108/bpmj-06-2014-0053
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation and evaluation of performance measurement model for the Thai frozen shrimp chain

Abstract: Purpose – The purpose of this paper is to investigate and evaluate the new performance measurement model for the Thai frozen shrimp chain. Design/methodology/approach – The performance measurement model was developed by the combination method between a structural equation modeling and an analytical hierarchy process, which the method confirmed and proved the construction of the framework and identified the important key performance indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In the literature, food safety is considered as one of the sub-components of quality (Pungchompoo and Sopadang, 2015), and is rarely regarded as a main criterion such as price and quality in any supplier selection work (Lau et al, 2018;Govindan et al, 2018). Yet, while a product of lower quality can still be sold at a lower price as compared to a product of higher quality (Grunert, 2005), a product with food safety risks would not be preferred by customers and consumers at all, regardless of the price.…”
Section: Supplier Selection Criteriamentioning
confidence: 99%
“…In the literature, food safety is considered as one of the sub-components of quality (Pungchompoo and Sopadang, 2015), and is rarely regarded as a main criterion such as price and quality in any supplier selection work (Lau et al, 2018;Govindan et al, 2018). Yet, while a product of lower quality can still be sold at a lower price as compared to a product of higher quality (Grunert, 2005), a product with food safety risks would not be preferred by customers and consumers at all, regardless of the price.…”
Section: Supplier Selection Criteriamentioning
confidence: 99%
“…Food industries generally select a raw material supplier based on the supplier's price, flavor or location, as governments further emphasize the importance of considering qualitative and quantitative criteria, such as food safety and quality (Prusak et al, 2013). Quality includes using food technology to measure shelf-life, freshness, size, and taste, but it may have a specific meaning; in the chicken meat chain, for example, quality aspects change according to the perception of the players in the chicken meat chain (Ali et al, 2017).…”
Section: Theoretical Background For Supplier Selection Processmentioning
confidence: 99%
“…However, food security, when addressed, is incorporated as part of quality, not being assessed at the first level and separately as other criteria (e.g. delivery time, price and quality) (Pungchompoo & Sopadang, 2015;Nakandala et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the findings from the measurement model showed that the conceptual model was a depiction of the data collected for the study. Pungchompoo and Sopadang (2015) observed that, once a good fit is obtained for a hypothesized model, the path significance of each association in the research model and the variance ought to be estimated. The path modelling, and its hypotheses testing are interpreted in the next section.…”
Section: Model Fit Summarymentioning
confidence: 99%